Public Policy on Entrepreneurship Education in the Independent Curriculum Based on Aquaculture Entrepreneurship Values - Tui, Fenti Prihatini Dance; Rahmatiah; Naufal R. Races; Abdussamad, Juriko (Universitas Pendidikan Ganesha, 2024)
In the era of globalization and digital transformation, the need for human resources who have the ability to adapt, innovate and entrepreneurship skills is increasing. This research aims to analyze the design of public policy in the field of entrepreneurship education in the Merdeka Curriculum in class X Social Sciences subjects, with a focus on integrating the values of fish farming entrepreneurship. The research method used is qualitative. Data collection techniques were carried out using observation, interviews and documentation. The research subjects are policy makers in the education sector. Data analysis is carried out by data reduction, data presentation, and drawing conclusions or verification. The research results show that the integration of fish farming values, such as social values, tenacity values, patience values, independent learning values, diligence values, and innovation values, into the Merdeka Curriculum can equip students with relevant practical skills. Applying a project approach allows students to be directly involved in managing fish farms to strengthen technical and managerial skills. This research also highlights the importance of forming entrepreneurial character, such as hard work and mental resilience, through contextual entrepreneurial activities. Policy support from local governments, including the provision of facilities and market access. This research provides recommendations for public policy in the field of entrepreneurship education based on pond entrepreneurial values in Pohuwato Regency. The novelty of this research is the design of public policy regarding the integration of fish farming values in the Merdeka Curriculum in the local context of Pohuwato, and implementation strategies based on local potential.